Navigating Financial Behavior: How Literacy, Herding, Risk Perception, and Attitude Shape Generation Z's Investment Decision - Mar’atus Zahro; Rika Rahayu; Triyonowati Triyonowati; Suhermin Suhermin; Okto Aditya Suryawirawan (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
In Indonesia, numerous young retail investors exhibit a lack of adequate financial knowledge and comprehension of investment fundamentals, potentially resulting in suboptimal investment choices and heightened financial exposure. This research seeks to examine how financial literacy, herding, risk perception, and attitude toward investment can enhance the decision-making process for students in investments, enabling them to make more educated and self-assured selections in financial markets. The study employed non-probability purposive sampling, involving 84 Generation Z participants. Data analysis was conducted using Partial Least Square (PLS) via SmartPLS. The findings reveal that financial literacy positively and significantly influences investment decision-making. Conversely, herding does not have a substantial impact on investment choices. Risk perception demonstrates a significant negative effect on investment decision-making, whilst attitude towards investment shows a significant positive influence. The study also found that attitude towards investment does not mediate the relationship between financial literacy and investment decision-making, nor does it mediate the impact of risk perception on investment decisions. However, it does mediate the influence of herding on investment decision-making. These outcomes contribute to a more comprehensive understanding of how each antecedent variable affects the decision-making processes of Generation Z students, offering valuable insights for educators, policymakers, and financial institutions aiming to improve investment education and support for young investors.